Study Regarding the Performance of the Romanian Banking System (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
Bank performance is an indicator of the quality management and soundness of commercial banks. The systemic role of the commercial banks in the Romanian economy and their role of main creditor determine the supervisors to monitories their performance and their capacity to face the challenges. Taking into account that we are talking about a banking system which has not yet exceeded during turbulence generated by economic and financial crisis, the aim of this study is to identify and analyze the main determinants of bank performance, so any shocks that may impact on this indicator to be identified early and minimized. The financial authorities, in their attempt to avoid new bank failures, because of their negative impact on the entire financial system, have imposed new capital requirements in order to strengthen the banking system’ capacity to absorb shocks. The most used indicators in order to measure the performance of the banking system are return on assets and return on equity. Taking into accounts this consideration the main objective of this study is to analyze the determinants that have a major impact on the banking system performance in an empirical and theoretical manner. To achieve this goal we used a quantitative method, the Pearson’s coefficient. Into the model were involved datas recorded by Romanian banking system in the period 2008-2013, processed by the publications of National Bank, the International Monetary Fund and the National Institute of Statistics. In the model of the correlation coefficient, the regression involved the following indicators: solvency, nonperforming loans as a percentage of total loans, gross domestic product and inflation. The results demonstrated that the factor that have the greatest impact on banking performance is the solvency ratio, followed by the nonperforming loans, the inflation rate and by the gross domestic product. So it can be observe that internal determinants have a biggest impact on the performance than the external one.